A Population-Based Study of COVID-19 Infection Among Childhood Cancer Survivors - Agha, Mohammad; Leung, Felicia; Moineddin, Rahim; Bradley, Nicole M.; Gibson, Paul J.; Hodgson, David C. (Frontiers in Medicine, 2021)
Childhood cancer survivors are known to be at risk of chronic co-morbidities, although their risk of COVID-19 infection remains uncertain. Understanding the risk of COVID-19 in this population is necessary to counsel survivors and inform potential mitigation strategies. The objective of this study was to determine whether the rates of COVID-19 infection differed between childhood cancer survivors and the general population. Administrative health care data from a population-based registry of children and adolescents diagnosed with cancer in Ontario, Canada, were linked with a universal health insurance registry and a repository of laboratory data. Rates of COVID-19 testing, test positivity and infection between March 1, 2020 and March 31, 2021 among childhood cancer survivors (n = 10 242) were compared to matched controls from the general population (n = 49 068). Compared to the general population, childhood cancer survivors were more likely to have COVID-19 testing (35.9% [95% CI, 34.5–37.4%] vs. 32.0% [95% CI, 31.4–32.6%]), but had a lower likelihood of positive COVID-19 result among those tested (4.3% [95% CI, 3.6–4.9%] vs. 5.5% [95% CI, 5.1–5.8%]) and a similar rate of infection among all subjects at risk (1.5% [95% CI, 1.3–1.8%] vs. 1.7% [95% CI, 1.6–1.9%]). These findings can inform counseling of survivors and clinician recommendations for this population.